2020
DOI: 10.1037/fam0000590
|View full text |Cite
|
Sign up to set email alerts
|

Couple relationship quality and the infant home language environment: Gender-specific findings.

Abstract: Couple relationship quality is known to drop significantly across the transition to parenthood (Ahlborg & Strandmark, 2001;Doss, Rhoades, Stanley, & Markman, 2009), yet individual differences in the amount of parent-to-infant talk have rarely been studied in relation to variation in couple relationship quality. Addressing this gap, the current study of 93 first-time parents with 4-month-old infants included multimeasure reports of couple relationship quality from both mothers and fathers and examined associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…That is, relationships characterized by high levels of satisfaction and low levels of conflict may be a place of solace for new mothers experiencing difficulties in learning how to respond sensitively to their infants' distress cues. Our nuanced findings mirror results from a subsample of 93 families who took part in in-depth recordings of their family-talk environment at 7-months ( 48 ). Specifically, compared with mothers of daughters, mothers of sons who reported less satisfaction and more conflict in their relationship with their partner used more infant-directed speech.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…That is, relationships characterized by high levels of satisfaction and low levels of conflict may be a place of solace for new mothers experiencing difficulties in learning how to respond sensitively to their infants' distress cues. Our nuanced findings mirror results from a subsample of 93 families who took part in in-depth recordings of their family-talk environment at 7-months ( 48 ). Specifically, compared with mothers of daughters, mothers of sons who reported less satisfaction and more conflict in their relationship with their partner used more infant-directed speech.…”
Section: Discussionsupporting
confidence: 71%
“…Other analyses from this study sample have also revealed striking between-parent similarities in: (a) the interplay between difficult birth experiences and postnatal wellbeing ( 7 ); and (b) associations between prenatal symptoms of anxiety and depression and infant adjustment at 24-months ( 4 ). That said, day-long recordings of family talk in a subsample of these families showed more frequent maternal rather than paternal infant-directed speech at 7 months ( 48 ). Outside of this sample, there are inconsistent reports of gender-related contrasts in parent sensitivity [e.g., ( 74 , 75 )].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the sample were highly educated (83% of mothers and 74% of fathers had an undergraduate or higher degree), a minority of parents were from ethnic minority backgrounds (9% of mothers and 8% of fathers). All infants (52% male) were born healthy, as confirmed by midwife report, and, according to parent report on the Ages and Stages Questionnaire, showed typical development at 4 months of age (M = 4.16 months, SD = 0.50) when the postnatal speech sample was collected and at 7 months of age (M = 6.94 months, SD = 1.09) when the LENA measures were collected (for more information see Fink et al, 2019). Five-minute speech samples were completed by 92 mothers and 89 fathers prior to the birth of their child and by 88 mothers and 86 fathers at 4 months postpartum.…”
Section: Samplementioning
confidence: 85%
“…As open systems affected by developments in their environment, families constantly have to adjust and evolve. According to Fink et al (2019), family systems theory describes two contrasting processes: spillover and compensation.…”
Section: Parental Relationship Quality and Socio-emotional Developmentmentioning
confidence: 99%